Angular Range Analysis (ARA) and K-Means Clustering of Multibeam Echosounder Data for Determining Sediment Type - Fahrulian Fahrulian; Henry M Manik; Indra Jaya; Udrekh Udrekh (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Backscatter value was a key to determine seabed characteristic. Level of intensity or backscatter informed through seabed type. One approach was use to analyze seabed type based on the value of backscatter was Angular Range Analysis (ARA). ARA utilize influence of angle backscattering intensities. The aim of this research was to determine value of backscatter from the bottom and used to initial prediction of seabed. Extraction processes of raw data obtained by acoustic signal processing techniques. Analysis of backscatter data was conducted by using K-means method to look the proximity of the centroid backscatter value against other values. Backscatter intensity from this sites ranged from -41,93 dB to -27 dB. The range value divided into three major classes based on Wenworth scale classification. Substrate type in the study site consists of sand, silt, and clay. Grain size diameter of each type include: sand 0.122713 mm (phi = 3.02), silt 0.018171 mm (phi = 5.78) and clay 0.002690 mm (phi= 8.53). Based on this result, signal processing multibeam echosounder able to classify seabed backscatter values to determine the seabed type Keywords: Angular Range Analysis, multibeam echosounder, K-Means